Prognostic and clinicopathological significance of systemic inflammation response index in patients with hepatocellular carcinoma: a systematic review and meta-analysis - Zhang, Sunhuan; Tang, Zhining (Frontiers in Immunology, 2024)
Background: It is unclear whether the systemic inflammation response index (SIRI) can predict the prognosis of patients with hepatocellular carcinoma (HCC). Consequently, the present study focused on systematically identifying the relationship between SIRI and the prognosis of patients with HCC through a meta-analysis. Methods: Systematic and comprehensive studies were retrieved from PubMed, Web of Science, Embase, and the Cochrane Library from their inception to August 10, 2023. The role of SIRI in predicting overall survival (OS) and progression-free survival (PFS) in HCC was determined using pooled hazard ratios (HRs) and 95% confidence intervals (CIs). Odds ratios (ORs) and 95% CIs were pooled to analyze the correlations between SIRI and the clinicopathological features of HCC. Results: Ten articles involving 2,439 patients were included. An elevated SIRI was significantly associated with dismal OS (HR=1.75, 95% CI=1.52–2.01, p<0.001) and inferior PFS (HR=1.66, 95% CI=1.34–2.05, p<0.001) in patients with HCC. Additionally, according to the combined results, the increased SIRI was significantly related to multiple tumor number (OR=1.42, 95% CI=1.09–1.85, p=0.009) and maximum tumor diameter >5 cm (OR=3.06, 95% CI=1.76–5.30, p<0.001). However, the SIRI did not show any significant relationship with sex, alpha-fetoprotein content, Child-Pugh class, or hepatitis B virus infection. Conclusion: According to our results, elevated SIRI significantly predicted OS and PFS in patients with HCC. Moreover, the SIRI was significantly associated with tumor aggressiveness.